1767-1774(H.1181-1188)TARİHLİ HARPUT ŞER'İYYE SİCİLİ(METİN DEĞERLENDİRME VARAK 45-83) - BACA, DUYGU (Fırat Üniveristesi, 2013)
Giriş bölümünde şer?iyye sicilleri, Harput şer?iyye sicilleri hakkında bilgiler verdik ve tezin tanıtımını yaptık. Daha sonra tezdeki belgelerin kısa özetlerini verdik. En sonda da tezdeki belgelerin çevirisini verdik. Anahtar Kelimeler: Osmanlı, Şer?iyye Sicilleri, Şer? i Hukuk, Sicil, Harput, Harput Sicilleri.

Firstly, in introductory chapter we have given information about Court Records Register and Harput Court Records Register also promoted the thesis. Secondly, in main chapter we have given the short summaries of the letters in the thesis. Finally, in conslusion chapter given the translation of the letters in the thesis. Key Words: Ottoman, Court records register, Register, Harput, Harput Court Records Registers.
Harput Court Records Register dated on 1767/1774(H. 1181-1188) (Text assessment pages 45-83)
Keywords: Tarih